Agresivitas Mahasiswa UIN Maulana Malik Ibrahim Malang - Nawa Syarif Fajar; Ahmad Anton Fatoni; Ayu Ernawati; Ulfatus Zakiyah (Universitas Muhammadiyah Jember, 2020)
Aggression is often interpreted as a behavior that aims to hurt others both physically and verbally. This study uses a quantitative approach, the research technique used is a correlational technique that is a research model that intends to conduct research and assessment of the characteristics of a population through samples drawn from that population. Based on the findings of the researchers, spiritual intelligence has a positive and significant effect on the Aggressiveness of Students of Malang's Maulana Malik Ibrahim UIN which is indicated by a significance value of less than the level of significant ie 0.050 or (0,000 0.050) that the influence of spiritual intelligence on students' aggressive and significant, thus the higher the spiritual intelligence, the lower the aggressiveness of the UIN Student Maulana Malik Ibrahim